Acetic acid permeation through photovoltaic backsheets: Influence of the composition on the permeation rate. (July 2017) - Oreski, Gernot; Mihaljevic, Antonia; Voronko, Yuliya; Eder, Gabriele C.
Abstract: Acetic acid, which is formed during degradation of the most frequently used photovoltaic (PV) encapsulant ethylene vinyl acetate (EVA), is linked to several PV module failure mechanisms like corrosion of interconnectors, cells or potential induced degradation (PID). An evaluation of a new measurement technique and data analysis for acetic acid permeation through photovoltaic backsheet films is described. The influence of the layer composition of the multilayer backsheets on the acetic acid permeation rates (AATR) was determined by investigating the permeation properties of the individual layers as well as the whole polymeric multilayer composites. Various polymeric backsheet types based on PET-core layers showing a very high barrier for acetic acid permeation were compared to fully polyamide material stacks which allow for a much higher transmission of acetic acid through the backsheet out of the module. Incorporated Al-layers were found to not affect the AATRs of PET based backsheets.